2022
DOI: 10.1371/journal.pone.0266650
|View full text |Cite
|
Sign up to set email alerts
|

The health impacts of a 4-month long community-wide COVID-19 lockdown: Findings from a prospective longitudinal study in the state of Victoria, Australia

Abstract: Objectives To determine health impacts during, and following, an extended community lockdown and COVID-19 outbreak in the Australian state of Victoria, compared with the rest of Australia. Methods A national cohort of 898 working-age Australians enrolled in a longitudinal cohort study, completing surveys before, during, and after a 112-day community lockdown in Victoria (8 July– 27 October 2020). Outcomes included psychological distress, mental and physical health, work, social interactions and finances. Reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Notably, equivalent levels of distress were observed in Victoria and other states prior to the lockdown, suggesting that the different states did not differ appreciably with respect to ongoing trends in psychological distress. During the period when lockdown was in effect in Victoria, however, symptoms of both anxiety and depression were significantly higher than in other states [ 26 , 27 ]. In addition, a national lockdown was imposed in New Zealand in 2020.…”
Section: Lockdowns Quarantines and Stay-at-home Orders In The Ukmentioning
confidence: 99%
“…Notably, equivalent levels of distress were observed in Victoria and other states prior to the lockdown, suggesting that the different states did not differ appreciably with respect to ongoing trends in psychological distress. During the period when lockdown was in effect in Victoria, however, symptoms of both anxiety and depression were significantly higher than in other states [ 26 , 27 ]. In addition, a national lockdown was imposed in New Zealand in 2020.…”
Section: Lockdowns Quarantines and Stay-at-home Orders In The Ukmentioning
confidence: 99%
“…It was reported that many community members were not able to prioritise the work of RESPOND as they were being pulled in other directions and began to have more focus on addressing the mental health impacts of these shocks on communities. COVID-19 has been reported to increase psychological distress, and adversely impact mental and physical health among others [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Victoria experienced the longest COVID-19 restrictions in Australia with six lockdowns (total 262 days in the capital city, Melbourne) across 2020-2021 impacting delivery of primary care, hospital procedures and capacity constraints, including reduced endoscopy and visitor limits. 16,18,21,22 Australian citizens and permanent residents have access to universal public healthcare, Medicare, with the option to purchase additional insurance for private hospital and specialist care. 23 GP appointment costs are fully or partially covered by Medicare, with patients paying out-of-pocket costs in the latter instance.…”
Section: Contextmentioning
confidence: 99%